Changing Facets of Pilgrimage Through Contemporary Tourism: Continuity & Transformations (With Special Reference to Madhya Pradesh, India) - Dr Preeti Singh (The Bioscan, 2026)
Bharat that is India, is a nation of diverse diasporas, having varied cultures, religions, ethnicities and languages & dialect. Some of its various States are better known for their religious and pilgrimage importance – like Gaya, Jagannath Puri, Tirupati Balaji, Kedarnath, Kashi Vishwanath, Mahakaal, Omkareshwar to name a few.